2016
DOI: 10.1177/0021998315623081
|View full text |Cite
|
Sign up to set email alerts
|

Development of press-and-sinter Al2024-based nanocomposites reinforced with multiwalled carbon nanotubes

Abstract: To fabricate large-scale multi-walled carbon nanotube-reinforced aluminum matrix composites, in this study, nanocomposites powder is successfully consolidated with simple processing methods. Ball milling is used to disperse multi-walled carbon nanotubes in the aluminum alloy 2024 matrix, and sequential cold press, hot press, and sintering techniques are selected for fabricating fully dense samples. As a result, an aluminum alloy 2024 composite with 4 vol.% multi-walled carbon nanotubes shows a yield strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Morphologies of initial MWCNT and FLG powders displayed in were not observed on the Al2024 powder surface because the MWCNT and FLG are inferred to be embedded and dispersed inside the Al2024 powder during milling [32,33]. The elevated temperature compressive true stressetrue strain curves of the Al2024/ 5MWCNT and Al2024/0.5FLG composites in the temperature range of 250e430 C with initial strain rate of 1 Â 10 À3 s À1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Morphologies of initial MWCNT and FLG powders displayed in were not observed on the Al2024 powder surface because the MWCNT and FLG are inferred to be embedded and dispersed inside the Al2024 powder during milling [32,33]. The elevated temperature compressive true stressetrue strain curves of the Al2024/ 5MWCNT and Al2024/0.5FLG composites in the temperature range of 250e430 C with initial strain rate of 1 Â 10 À3 s À1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…∼55.5 GPa/(mg/m 3 ) of all materials, ultrahigh Young’s modulus (∼1 TPa), tensile strength (∼150 GPa), thermal stabilities (stable up to 2527 K in vacuum), and excellent electrical conductivity for production of novel MMCs. 46 In order to attain high strengthening effect in AMMCs, CNTs are proposed as a novel reinforcement material for aluminum (Al)-based MMCs to carry out effective load transfer through the contact of Al–CNT interface.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pore filling played an important role in the sintering densification process of aluminum. SE Shin et al 4 showed that Al2024-based nanocomposites reinforced with multiwalled carbon nanotubes were successfully consolidated by press and sintering. A Gökçe et al 5 illustrated the sintering behavior of aluminum elemental mixed powder, and the compacts with good microstructure and high strength were obtained.…”
Section: Introductionmentioning
confidence: 99%